2017
DOI: 10.1037/scp0000123
|View full text |Cite
|
Sign up to set email alerts
|

Neuroanatomical correlates of familial risk-for-depression and religiosity/spirituality.

Abstract: Objective To examine potential neural substrates that underlie the interplay between religiosity/spirituality and risk-for-depression. A new wave of data from a longitudinal, three generation study of individuals at high risk for depression is presented. In addition to providing new longitudinal data, we extend previous findings by employing additional (surface-based) methods for examining cortical volume. Measures, Participants, and Methods Magnetic resonance imaging (MRI) scans were collected on 106 second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 44 publications
4
10
0
1
Order By: Relevance
“…The present report evaluated whether individuals at high familial risk for major depression, who rated religion and spirituality as highly important during adolescence and young adulthood, differed in their early, bottom-up processing of unpleasant pictures during an emotional hemifield paradigm (Kayser et al, 2016(Kayser et al, , 2017. In agreement with prior studies (Miller et al, 2012(Miller et al, , 2014Svob et al, 2016;Liu et al, 2017), R/S importance significantly modulated outcome measures dependent on risk status. Here, overall early emotional ERP responsivity and asymmetry, which was observed for low R/S importance participants independent of risk status, was substantially diminished or absent for high risk individuals with high R/S importance; however, it was enhanced for low risk individuals with high R/S importance.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The present report evaluated whether individuals at high familial risk for major depression, who rated religion and spirituality as highly important during adolescence and young adulthood, differed in their early, bottom-up processing of unpleasant pictures during an emotional hemifield paradigm (Kayser et al, 2016(Kayser et al, , 2017. In agreement with prior studies (Miller et al, 2012(Miller et al, , 2014Svob et al, 2016;Liu et al, 2017), R/S importance significantly modulated outcome measures dependent on risk status. Here, overall early emotional ERP responsivity and asymmetry, which was observed for low R/S importance participants independent of risk status, was substantially diminished or absent for high risk individuals with high R/S importance; however, it was enhanced for low risk individuals with high R/S importance.…”
Section: Discussionsupporting
confidence: 54%
“…High R/S importance was also associated with less cortical thinning (Miller et al, 2014), a putative morphologic endophenotype of familial risk for MDD (Peterson et al, 2009). Further implicating protective benefits of R/S importance for persons at high risk for depression, those who self-reported high R/S importance, when compared those who did not, had larger pial surface representing the outer boundary area between gray matter and cerebrospinal fluid (Liu et al, 2017). Moreover, posterior EEG alpha oscillations at rest, a putative biomarker of antidepressant treatment response (Tenke et al, 2011), was greater in individuals who rated R/S as highly important compared to those who did not, provided ratings were obtained during early stages of ontogenetic development (Tenke et al, 2013(Tenke et al, , 2017.…”
Section: Introductionmentioning
confidence: 93%
“…We next tested the neurobiological underpinnings of R/S in families at high and low risk for depression. We found that belief in the importance of R/S was associated with thicker cortices in bilateral parietal and occipital regions, particularly the cuneus and precuneus (Liu et al, ; Miller et al, ). As we had previously reported cortical thinning in these regions as a stable biomarker for depression risk (Hao et al, ; Peterson et al, ), we hypothesized that the thicker cortices in those reporting high importance of R/S beliefs may serve as a compensatory or protective mechanism.…”
Section: Introductionmentioning
confidence: 95%
“…R/S importance (i.e., How important to you is religion or spirituality ?) is often associated with protective effects—presumably independently of religious service attendance and religious affiliation, which have also proven beneficial [27]–and this has been particularly true in our studies [816]. As such, we were motivated to investigate what underlies the largely subjective and complex construct of R/S importance.…”
Section: Introductionmentioning
confidence: 95%
“…For example, we found high self-report ratings of R/S importance to be protective against recurrence of depression [11] and childhood suicidal behaviors [12]. We have also observed protective effects of R/S importance in biomarkers of high-risk as compared to low-risk families, including decreased default mode network connectivity [13], thicker cortices [89], and greater posterior EEG alpha [1516]. Moreover, these effects were transmitted across generations for both depression [10] and suicidal behavior [14], and extended to correlates of genetic markers [17].…”
Section: Introductionmentioning
confidence: 99%